Quimantú mini books: a world between pulp literature and socialist realism - Bascuñán, Patricio (Universidad de Chile. Facultad de Filosofía y Humanidades, 2020)
In this essay will be analyzed the literary world that unfolds in the collection Minilibros of the National Publishing Company Quimantú (1971-1973), during the goverment of the Unidad Popular in Chile, paying attention to its commitment to create new masses of readers through an easy-to-understand world literature . We reffer to a repertoire of works of diverse genres such as adventure, drama and science fiction, which can be understood under the category of pulp literature,, which mostly circulated through low-cost North American publications in the early twentieth century, which they orchestrate together with Russian and Latin American works of marked realistic character. This opens up questions about the motivations of the publishing house, belonging to a socialist and Latin American political project, for offering an opening to the world largely crossed by elements of an American mass culture